2014
DOI: 10.1093/nar/gku764
|View full text |Cite
|
Sign up to set email alerts
|

A competitive formation of DNA:RNA hybrid G-quadruplex is responsible to the mitochondrial transcription termination at the DNA replication priming site

Abstract: Human mitochondrial DNA contains a distinctive guanine-rich motif denoted conserved sequence block II (CSB II) that stops RNA transcription, producing prematurely terminated transcripts to prime mitochondrial DNA replication. Recently, we reported a general phenomenon that DNA:RNA hybrid G-quadruplexes (HQs) readily form during transcription when the non-template DNA strand is guanine-rich and such HQs in turn regulate transcription. In this work, we show that transcription of mitochondrial DNA leads to the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 38 publications
5
64
0
Order By: Relevance
“…An RNA/DNA G4 at CSBII202122 suggests a functional role in contributing to R-loop stabilization, similar to that observed in nuclear DNA51. Numerous additional G4s are predicted along the mtDNA sequence151617 and may form during replication, leading to genomic instability5253.…”
Section: Discussionmentioning
confidence: 64%
“…An RNA/DNA G4 at CSBII202122 suggests a functional role in contributing to R-loop stabilization, similar to that observed in nuclear DNA51. Numerous additional G4s are predicted along the mtDNA sequence151617 and may form during replication, leading to genomic instability5253.…”
Section: Discussionmentioning
confidence: 64%
“…They guide RNA processing in mitochondria (Ojala et al, 1981), and in giant viruses and their virophages (Byrne et al, 2009; Claverie and Abergel, 2009). This ubiquitous structural signaling also applies to RNA:DNA hybrids, which play a role in the origin-independent replication priming in eukaryotic cells (Stuckey et al, 2015) and in transcription termination in human mitochondria (Zheng et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the RNAdependent background was unexpected because the sequences were blasted to avoid homology with the human transcriptome. We found that these specific amplifiers contained guanine nucleotides in the 20-mer repeating sequences that might form hybrid G-quadruplex structures, which have been reported to bind to mitochondrial RNA 33 . The specific spatial distribution observed with the staining of these amplifiers (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…3c). Given the cellular distribution of this binding, we suspected these guanine-rich secondary amplifier sequences might form Gquadruplex structures with mitochondrial RNAs 33 . In parallel, we observed a small number of amplifier pairs that assembled with much lower efficiency, producing only small degrees of amplification, perhaps due to low melting temperature or the formation of G-quadruplex structures that inhibit proper amplifier assembly ( Fig.…”
Section: Amplifier Screening For Merfish Imagingmentioning
confidence: 99%